Three-dimensional reconstruction and connectivity analysis of REV-size organic matter in shales - Liu, Dongchen; Yang, Xuefeng; Zhao, Shengxian; Zhang, Deliang; Huang, Shan; Zhu, Ning; Rong, Jianqi; Shi, Bowen; Wang, Zhiwei; Qin, Chao-Zhong (Frontiers in Earth Science, 2025)
Organic matter (OM) serves as a crucial site for shale gas generation and occurrence. Its content and spatial connectivity significantly influence gas flow ability and gas occurrence. However, in characterizing the three-dimensional (3D) connectivity of OM, current imaging techniques such as FIB-SEM and nano-CT cannot balance field of view (FoV) and image resolution. To address this gap, in this work, we develop a novel workflow for numerical reconstruction of REV-size digital rocks of OM that integrates high-resolution information of pore structures in large-view MAPS (modular automated processing system) images. Specifically, the open source code, SliceGAN, is used in the 3D reconstruction of digital rocks of OM, while the high-resolution information of OM pore structures is integrated into the digital rocks in terms of the classification of OM in the MAPS images. The classification of OM is solely based on the surface or 2D porosity of individual OM watersheds. As a first attempt, we propose three types of OM including Type A with high porosity (>20%), Type B with medium porosity (10%∼20%), and Type C with low porosity (<10%). Based on the case studies of three in-situ shale samples with different OM contents, we show that at the REV size the three types of OM, as a whole, can form conducting pathways throughout the domains, but each type of OM is disconnected. Type A and Type B OM have poor connectivity, while Type C OM holds the best connectivity dominating gas transport at the REV scale. Moreover, the reconstructed 3D digital rocks of OM can be used in the numerical modeling of REV-size gas transport in shales.